A Survey on Security Vulnerabilities in Wireless Ad Hoc High Performance Clusters. (2016) - Shivaramu, K.N.; Prasobh, P.S.; Poti, Nagaraj
Abstract: Wireless ad hoc high performance clusters extend the paradigm of contemporary wired cluster architectures to present the great possibility of achieving ubiquitous distributed computing in the near future. The explosion of mobile devices such as smart phones, tablets, laptops and wearable tech that are nearing workstation grade performance benchmarks make the concept of wireless clusters a reality. However, the physical characteristics of the wireless medium and distributed nature of computing gives rise to many targeted security vulnerabilities that need to be properly identified and addressed. This paper presents a survey on security issues, threats, challenges and contingency measures that are suitable to reduce the risk of occurrence and impact should such threats materialize. Security issues that impact battery life of nodes, performance of the cluster and data integrity are analyzed carefully, culminating in a general policy and architecture proposal for establishing node trust in wireless clusters.